Clinicopathologic Features and Treatment of CD10-Positive Mantle Cell Lymphoma: A Case Report and Review of Literature - Christopher Hino; Bryan Pham; Austin L. Gray; Jun Wang; Dan Ran Castillo; Mojtaba Akhtari; Yan Liu (Frontiers Media S.A., 2022)
Mantle cell lymphoma (MCL) is a rare and aggressive non-Hodgkin's B cell lymphoma characterized by the translocation t(11;14) (q13;32) and overexpression of CCND1. MCL is immunophenotypically identified as CD20+, CD5+, CyclinD1+, CD43+, CD10−, BCL6−, and CD23−. It is often distinguished from B cell lymphomas of germinal center cell origin by the absence of CD10 expression. Here we report the unique clinicopathologic features of a patient with CD10+ MCL with gastrointestinal involvement and review current literature identifying this unique immunophenotype.